2020
DOI: 10.1155/2020/2170750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Botulinum Toxin Type A on Microvessels in Hypertrophic Scar Models on Rabbit Ears

Abstract: Background. Although Botulinum Toxin Type A (BTXA) has been applied to scar prevention and treatment, the mechanisms still require further exploration. Objective. To investigate the effects of BTXA on microvessels in the hypertrophic scar models on rabbit ears. Methods. Eight big-eared New Zealand rabbits (males or females) were selected to establish scar models. One ear of each rabbit (4 models in each ear) was selected randomly to be injected with BTXA immediately after modeling and included in the treated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Ten articles did not provide detailed data. Thus, 11 articles were included in the analysis 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles did not provide detailed data. Thus, 11 articles were included in the analysis 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…56,57 Other profibrotic factors, including interleukin-6, connective tissue growth factor, and vascular endothelial growth factor (VEGF), were also downregulated, 55 and angiogenesis was inhibited in parallel. 58,59 BTXA attenuated the scar contraction through negatively affecting the expression of α-smooth muscle actin and myosin II in fibroblasts. 53,54,60,61 Collagen deposition and remodeling processes were likewise altered in response to BTXA.…”
Section: Discussionmentioning
confidence: 96%
“…TGF‐β/Smad and ERK pathways could be the signaling pathway mediating BTXA function, 54 and meanwhile, other pathways, such as PTEN and JNK pathways, were also proposed to contribute to the inhibitor effect of BTXA on fibroblasts 56,57 . Other profibrotic factors, including interleukin‐6, connective tissue growth factor, and vascular endothelial growth factor (VEGF), were also downregulated, 55 and angiogenesis was inhibited in parallel 58,59 . BTXA attenuated the scar contraction through negatively affecting the expression of α‐smooth muscle actin and myosin II in fibroblasts 53,54,60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, scar hyperplasia is related to the creation of scar vessels, and vascular endothelial growth factor (VEGF), angiogenin, and basic fibroblast growth factor are all involved in scar vessel forming. In a rabbit ear model, Zhou 24 demonstrated that BTXA injection reduced angiogenesis and prevented the formation of hypertrophic scars by inhibiting the expression of related cytokines such as VEGF.…”
Section: Scar-associated Cytokinesmentioning
confidence: 99%